QUALITY OF SERVICE AND ACCESSIBILITY OF HEALTH SERVICES AND ITS IMPLICATIONS ON PATIENT COMPLIANCE THROUGH PATIENT SATISFACTION AS AN INTERVENING VARIABLE IN THE MEDICAL REHABILITATION POLYCLINIC OF KEPULAUAN MERANTI DISTRICT HOSPITAL - Sanjani, Ravi; Sidqi, Abdul Gani; Wirawan, Chevie (International Journal of Cultural and Social Science, 2025)
This study is driven by the need to improve healthcare service quality to achieve patient satisfaction and compliance, particularly in medical rehabilitation, which plays a key role in restoring function for patients with chronic illnesses, disabilities, or injuries. Service quality includes promotive, preventive, curative, and rehabilitative aspects as mandated by Law No. 44/2009. Previous studies show that the SERVQUAL dimensions strongly influence satisfaction and patient behavior. At Kepulauan Meranti Regional Hospital, low patient compliance and declining outpatient visits remain major issues, worsened by limited rehabilitation facilities. Using a quantitative method with an associative and cross-sectional design, this study examined the effect of service quality and accessibility on patient satisfaction and adherence. The results indicated that service quality had a significant positive effect on satisfaction, while accessibility did not. Satisfaction significantly influenced adherence and acted as an intervening variable. Overall, the model explained only 25.7% of the variation in patient adherence.